Synergistic Effect of MWCNT and Carbon Fiber Hybrid Fillers on Electrical and Mechanical Properties of Alkali-Activated Slag Composites - Hyeong Min Park; Chanho Park; Jinho Bang; Minwook Lee; Beomjoo Yang (Crystals, 2020)
Herein, we investigated the synergistic effect of multi-walled carbon nanotube (MWCNT) and carbon fiber (CF) hybrid fillers on electrical and mechanical characteristics of alkali-activated slag (AAS) composites. Many studies on AAS composites have been conducted in the past; however, not much progress has been made regarding characteristics of AAS composites with hybrid conductive fillers. The specimens with different mix proportions were fabricated in the present study, and numerous material characteristics, including flowability, electrical resistivity, and compressive strength of AAS composites were measured. In addition, the synergistic effects were investigated through scanning electron microscopy and thermogravimetric analysis. It was found that the 0.5 wt.% of MWCNTs and CFs lead the effects of the bridging and reducing crack propagation, thereby improving its electrical and mechanical performances. The filler exceeding a percolation point improved the electrical performance of the AAS composites; however, it interfered with the hydration process during the curing period, and caused a decrease in compressive strength of AAS composites.